EFFECT OF THE ADDITION OF FRUIT JUICES ON GRAPE MUST FOR NATURAL BEVERAGE PRODUCTION - L. Chiusano; M.C. Cravero; D. Borsa; C. Tsolakis; G. Zeppa; V. Gerbi (Chiriotti Editori, 2015)
The consumer attention for products with healthy properties is increased in time, and fruit juices, for their ease of consumption, can satisfy this demand providing them bioactive compounds. The grape juice has numerous health benefits demonstrated by several studies such as, among other, the antioxidant activities and the positive functions of their phenolic compounds. This work is aimed at blending grape and others fruits in a new fruit juice made only with natural ingredients of local production. The grape juice (cv Barbera) has substituted water and its percentage was fixed (70%). It was mixed with apple (cv Golden delicious), pear (cv Williams) and peach (cv Red Haven) juices to obtain 25 different prototypes. In each of these at least two fruit juices were present and added in a percentage variable from 0 to 25%, with a step of 5%. The objectives of this study were to check the feasibility of the mixing process and the evaluation of the samples overall pleasantness. Other sensory aspects of samples were also evaluated by consumers with a JAR (just-aboutright) structured scale. The results didn't reveal particular technological problems regarding the blending process. The Brix mean value of the samples was about 15.3, with a significant reduction compared to that of the grape juice (about 19). The pH mean value of the samples (3.44) was significantly higher than that of the grape juice (3.36). The titrable acidity and the antioxidant capacity mean value of the samples was, namely, 6.22 g L-1 and 535.18 mg L-1. The penalty analysis of the liking test pointed out the importance of the persistence in mouth. The overall pleasantness was significantly (p≤0,01) positively correlated with the °Brix/acid ratio (r=0.54) and samples with the highest percentage of pear juice were generally preferred.